Epigenetic reprogramming in pancreatic premalignancy and clinical implications - Zhang, Wei; Jiang, Tingting; Xie, Keping (Frontiers in Oncology, 2023)
Pancreatic cancer (PC) is the most lethal human cancer, with less than 10% 5-year survival. Pancreatic premalignancy is a genetic and epigenomic disease and is linked to PC initiation. Pancreatic premalignant lesions include pancreatic intraepithelial neoplasia (PanIN), intraductal papillary mucinous neoplasm (IPMN), and mucinous cystic neoplasm (MCN), with pancreatic acinar-to-ductal metaplasia (ADM) as the major source of pancreatic premalignant lesions. Emerging evidence reveals that an epigenetic dysregulation is an early event in pancreatic tumorigenesis. The molecular mechanisms of epigenetic inheritance include chromatin remodeling; modifications in histone, DNA, and RNA; non-coding RNA expression; and alternative splicing of RNA. Changes in those epigenetic modifications contribute to the most notable alterations in chromatin structure and promoter accessibility, thus leading to the silence of tumor suppressor genes and/or activation of oncogenes. The expression profiles of various epigenetic molecules provide a promising opportunity for biomarker development for early diagnosis of PC and novel targeted treatment strategies. However, how the alterations in epigenetic regulatory machinery regulate epigenetic reprogramming in pancreatic premalignant lesions and the different stages of their initiation needs further investigation. This review will summarize the current knowledge of epigenetic reprogramming in pancreatic premalignant initiation and progression, and its clinical applications as detection and diagnostic biomarkers and therapeutic targets in PC.